Someone had to do it eaudiobook - Brown, Amber (Harlequin Audio, 2022)
"A dark and riveting page-turner with an intelligent twist." —Nadine Matheson, author of The Jigsaw Man SOMEONE HAD TO MAKE HIM PAY. SOMEONE HAD TO TAKE HER DOWN. Brandi Maxwell is living the dream as an intern at prestigious New York fashion house Simon Van Doren. Except "living the dream" looks more like scrubbing puke from couture dresses worn by hard-partying models and putting up with microaggressions from her white colleagues. Still, she can't help but fangirl over Simon's it-girl daughter, Taylor. Until one night, at a glamorous Van Doren party, when Brandi overhears something she shouldn't have, and her fate becomes dangerously intertwined with Taylor's. Model and influencer Taylor Van Doren has everything...and is this close to losing it all. Her fashion mogul father will donate her inheritance to charity if she fails her next drug test, and he's about to marry someone nearly as young as Taylor, further threatening her stake in the family fortune. But Taylor deserves the money that's rightfully hers. And she'll go to any lengths to get it, even if that means sacrificing her famous father in the process. All she needs is the perfect person to take the fall... Don't miss Amber & Danielle Brown's next riveting thriller, ZETAS TILL WE DIE , where during their ten-year reunion Priscilla and her sorority sisters are forced to confront the secrets of their past when one of their sisters didn't survive the night... More thrillers from Amber & Danielle Brown: Perfect Little Lives